Islam dan Egalitarianisme: Ruang Terbuka Kesetaraan Gender - Itmam Aulia Rakhman (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2019)
Islam is a religion that inherently carries the spirit of egalitarianism. The facts about the variants of Islam that are central, formal and pure are egalitarian and scientific - while the hierarchy and existence are developing peripheral forms - help them adjust to the modern world. As a religion that carries an egalitarian spirit, Islam should put its people in various social issues - and of course religion - equally, without distinguishing between rich and poor, old and young, male and female. Because the "difference" between them is only the level of piety. In the sense of Egalitas doctrine maintains that in essence all human beings are the same in a fundamental value or moral status. Islam views all human beings as equal to God, there is no difference between one tribe and another. There is also no difference in human values ??between men and women because everything is created from a man and a woman.